Direct Observation Of Graphene During Raman Analysis And The Effect Of Precursor Solution Parameter On The Graphene Structures - Mohd Abid, Mohd Asyadi 'Azam; Abdul Aziz, Mohd Fareezuan; Zulkapli, Nor Najihah; Munawar, Rose Farahiyan; Mohd Suan, Mohd Shahadan; Safie, Nur Ezyanie; Omar, Ghazali (Elsevier Ltd, 2020)
Controlling the precursor solution parameter in preparing active catalyst film is critical in sol-gel process. The aim of this work is to validate the precursor solution parameter that affects the structural properties of graphene. Active Co3O4 film was prepared using precursor solution from cobalt acetate tetrahydrate in two different concentrations; 0.025 M and 0.05 M. One batch of the precursor solution was directly spin coated onto the substrate's surface meanwhile the second batch was kept for 4 days aging process. The studied spin speeds were 2000 rpm and 6000 rpm, and spin coated for 60 s. The active Co3O4 film was achieved by annealing at 450 °C and the graphene was grown at 900 °C of chemical vapor deposition (CVD) processing temperature for 5 min with the presence of ethanol as the carbon feedstock. The structural properties and morphology of the as-grown graphene synthesized from active Co3O4 film were characterized by Raman spectroscopy, optical microscope, and field emission scanning electron microscope (FESEM). The results demonstrated that concentration of precursor solution and the aging process affected the performance of the as-grown graphene. Agglomerates were formed in sample with 0.05 M of Co acetate tetrahydrate, however it was found that the Raman peaks intensity increased as compared to the 0.025 M sample. The precursor with 0.05 M has an acceptable chemical stability though aged for 4 days and contributed to the graphene growth. The spin coating speed was found not to affect the graphene growth at all. For aging effect, concentration 0.025 M shows unstable condition as compared to concentration 0.05 M when the precursor solution was aged for 4 days. Nonetheless, for the quality of the as-grown graphene, the ratio of Raman 2D-band over G-band intensities was less than 1.0, indicated that the graphene was in multi-layer form.